Analisis Faktor Individu Terhadap Tugas Kesehatan Keluarga Penderita Diabetes Melitus Di Wilayah Kerja Puskesmas Driyorejo Kabupaten Gresik - Dwi Ernawati; Nuh Huda; Amelia Kristina Merry Pitaloka (LPPM STIKes ICsada Bojonegoro, 2020)
ABSTRACT The family function as a support system for members suffering from Diabetes Melitus demands greater economic, social, and psychological sacrifice from the family. The inability of the family to carry out five family health tasks for people with DM can be caused by several factors, including family knowledge and family social economy. This is can be related to family health duties. The aim of this study is determine the relationship of individual factors to family health tasks that have been carried out on families of people with Diabetes Mellitus at Primary Health Center of Driyorejo Gresik . The design of this study used observational analytic methods. The sampling was done by cluster sampling method and obtained a sample of 67 respondents. Independent variables is individual factors while the dependent variable is family health tasks. Research instruments for individual factors were age, sex, education, occupation, duration of suffering from diabetes mellitus and family’s health tasks measuring by questionnaire. Analysis data with Spearman Rank test. The results of this study indicate that there is a relationship between individual factors consisting of age and education with the health assignments of families with diabetes mellitus patients. Spearman rank test results obtained p-value of 0.003 <0.05 at age, and 0.013 <0.05 in education. Health workers can improve health promotion to the community regarding ideal body weight monitoring, healthy living, routine blood sugar and family checkups to support diabetics to participate in health programs to prevent further complications of diabetes mellitus Keywords : Individual factors, family’s health tasks, Diabetes Mellitus